PENGARUH ARTIFICIAL INTELLIGENCE TOOLS TERHADAP MOTIVASI BELAJAR DITINJAU DARI TEORI ROGERS PADA SISWA KELAS IV MI QURANIAH IV PALEMBANG - Cahaya Putri Patimah; Farizal Imansyah; Murjainah (STKIP Subang, 2026)
This study aims to empirically examine the effect of using Artificial Intelligence (AI) Tools on the learning motivation of 4th-grade students at MI Quraniah IV Palembang, and to analyze it from the perspective of Carl R. Rogers' Humanistic Psychology Theory. This quantitative research employed a causal associative method with a total sampling technique consisting of 28 students. Data were collected through closed questionnaires and field observations, and analyzed using simple linear regression analysis via SPSS 25.The t-test results indicated a positive and significant effect of AI Tools on students' learning motivation, with tvalue > ttable (17.679 > 2.056) and a significance level of 0.000 < 0.05. The generated regression equation is Y = 1.416 + 0.825X. Based on the coefficient of determination (R^2) analysis, the R Square value reached 0.923, meaning that the use of AI Tools contributes a highly dominant 92.3% to the variance of students' learning motivation, while the remaining 7.7% is influenced by other factors outside this research model. This model was also declared highly fit based on the F-test value of 312.538. Viewed from Carl R. Rogers' theory, AI Tools boost motivation because they fulfill children's basic psychological needs in learning. The personalized material features satisfy the principle of Freedom to Learn, the non-judgmental and instant feedback establishes Psychological Safety, and the accumulation of both drives students' Self-Actualization. Despite the powerful influence of technology, moral guidance and emotional affection from teachers remain essential factors that cannot be replaced by AI algorithms.